Designing User Interface Of Travel Mobile Application Based On Artificial Intelligence - Nielson Teo Indrawan; Evelyne Henny Lukitasari; Ahmad Khoirul Anwar (Green Publisher Indonesia, 2024)
Indonesia is a country with many potential places that can be used as tourist destinations. The Central Statistics Agency (BPS) states that as of 2021 Indonesia has a total of 2,552 destinations in the tourism industry. The development of the tourism industry in Indonesia was hampered by the pandemic that had hit the country for approximately 2 years, which caused a narrow space for tourists to move. On the other hand, the use of digital technology has increased during the pandemic era. Artificial intelligence is one of the technologies that also developed during the pandemic. This technology allows for a program to think like a human and help facilitate daily activities and work. This design has the aim of creating an application display design that can implement artificial intelligence in a mobile application for the needs of the tourism industry. The method used in this design is the Design Thinking method popularized by Kelley and Brown from IDEO, consisting of the Emphatize, Define, Ideate, Prototype, and Testing stages. The result of this design is a design of a mobile application interface for the tourism industry, with the implementation of artificial intelligence and various features, and contains information about various tourist destinations, as well as designing its trials easily by users.